'Channeling' therapeutic discovery for epileptic encephalopathy through iPSC technologies. (May 2022) - Simkin, Dina; Ambrosi, Christina; Marshall, Kelly A.; Williams, Luis A.; Eisenberg, Jordyn; Gharib, Mennat; Dempsey, Graham T.; George, Alfred L.; McManus, Owen B.; Kiskinis, Evangelos
Abstract : Induced pluripotent stem cell (iPSC) and gene editing technologies have revolutionized the field of in vitro disease modeling, granting us access to disease-pertinent human cells of the central nervous system. These technologies are particularly well suited for the study of diseases with strong monogenic etiologies. Epilepsy is one of the most common neurological disorders in children, with approximately half of all genetic cases caused by mutations in ion channel genes. These channelopathy-associated epilepsies are clinically diverse, mechanistically complex, and hard to treat. Here, we review the genetic links to epilepsy, the opportunities and challenges of iPSC-based approaches for developing in vitro models of channelopathy-associated disorders, the available tools for effective phenotyping of iPSC-derived neurons, and discuss the potential therapeutic approaches for these devastating diseases. Highlights: Mutations in ion channel genes account for approximately 45% of all cases of genetic epilepsy. Modeling channelopathy-associated epilepsy using iPSC technology provides access to human neurons and requires strict quality control measures. A range of technologies can be effectively used for physiological and pharmacological assessment of iPSC-derived patient neurons in cell culture models, including advanced functional measurements and ‐omics based tools. iPSC-based models for channelopathy-associated epilepsy can be used to develop and assess potential therapeutics such as small molecules, antisense oligonucleotides and gene-therapy approaches.